Child Health Monitoring Description in MCTS at Ranuyoso PHC Lumajang - Bettis Wijayanti (Universitas Airlangga, 2017)
Infant Mortality Rate in Lumajang was always higher than the infant mortality rate in East Java Province. Ranuyoso is a region with the highest infant mortality rate and AKABA in 2013 and 2014, with 33 and 22 deaths. The Government had implemented a program to improve the health and the consolidation scope is monitored by the Pemantauan Wilayah Setempat Kesehatan Ibu dan Anak (PWS KIA). PWS KIA had not been going well according to its purpose as a tool for monitoring the KIA service coverage to increase the range and quality of KIA services. The purpose of this research was to describe the implementation of PWS KIA for indicators of child in Health Center of Ranuyoso which based on attributes of simplicity, acceptability, sensitivity, representativeness, data quality, timeliness and stability. This research used descriptive method evaluative with coordinator midwife, midwives health center and eight village midwives as the respondent. Description based on the attributes of surveillance system showed that PWS KIA indicator of child in Health Center of Ranuyoso was not simple, sensitive but not supported well by the midwives, the data were less quality, not timely and unstable. Alternative solutions to problems that had been found were to performing the advanced analysis to determine the causality amount variables by midwives, holding routine supervision from the senior midwives, procurement of SOP or guidebook for midwives, and computerizing the recording until reporting start from village midwives, also the making of the attendance and expeditions book to record the reporting date of midwives.   Keywords: MCTS, attributes surveillance, child health monitoring